2018
DOI: 10.1007/s12551-018-0430-7
|View full text |Cite
|
Sign up to set email alerts
|

At the heart of inter- and intracellular signaling: the intercalated disc

Abstract: Proper cardiac function requires the synchronous mechanical and electrical coupling of individual cardiomyocytes. The intercalated disc (ID) mediates coupling of neighboring myocytes through intercellular signaling. Intercellular communication is highly regulated via intracellular signaling, and signaling pathways originating from the ID control cardiomyocyte remodeling and function. Herein, we present an overview of the inter- and intracellular signaling that occurs at and originates from the intercalated dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 123 publications
1
34
0
Order By: Relevance
“…Interestingly, stronger contractions of the cell scaffolds were observed for the treatment groups. Such contractions are an indication of intercalated discs, which are composed of gap junctions, adherent junctions, and desmosomes between the cardiomyocytes [67]. This was confirmed using TEM, showing the presence of the different structures ( Figure 2F).…”
Section: Cardioprotectionsupporting
confidence: 55%
“…Interestingly, stronger contractions of the cell scaffolds were observed for the treatment groups. Such contractions are an indication of intercalated discs, which are composed of gap junctions, adherent junctions, and desmosomes between the cardiomyocytes [67]. This was confirmed using TEM, showing the presence of the different structures ( Figure 2F).…”
Section: Cardioprotectionsupporting
confidence: 55%
“…The intercalated disc is formed from the juxtaposition of the sarcolemma membranes from adjacent cardiomyocytes and enables the cells to be mechanically and electrically coupled together [ 37 ]. It has a complex inter-digitated ‘plicate’ structure that ensures the inter-cellular connections are both close and continuous.…”
Section: The Nav Channel β-Subunits As Cell-adhesion Moleculesmentioning
confidence: 99%
“…It has been reported that γ-catenin is rapidly degraded when expressed in a fibroblast model system in the absence of interactions with either desmoglein or desmocollin (Kowalczyk et al, 1994). As a member of the armadillo family of proteins and a paralog of β-catenin, γ-catenin also participates in cell signaling in addition to its role as a structural protein (Manring et al, 2018). The protein level of γ-catenin was dramatically decreased during CVB3 infection and no significant amount of cleaved products was observed in our Western blot analysis.…”
Section: Discussionmentioning
confidence: 63%